1999
DOI: 10.1016/s0895-7061(99)00094-1
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy in postmenopausal women with essential hypertension increases circulating plasma levels of bradykinin

Abstract: Hormone replacement therapy (HRT) reduces the incidence of cardiovascular disease (CVD) in postmenopausal women (PMW). Recently, it has been reported that HRT declines angiotensin converting enzyme (ACE) activity, which may be one of the factors protecting against CVD. We measured the plasma levels of bradykinin, which would be expected to increase because the bradykinin-degrading enzyme (kinase II) is the same as ACE. Treatment with conjugated estrogens (0.625 mg/day) and medroxyprogesterone (2.5 mg/ day) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…In the present study, the degree of ERT-induced ACE inhibition was similar in NPW and HPW. Interestingly, Sumino et al 20 have recently reported that ERT increases the plasma concentration of bradykinin to a greater extent in HPW than in NPW, whereas the ERTinduced reduction in serum ACE activity was similar in NPW and HPW. We hypothesize that HPW might have higher bradykinin concentrations after ERT, resulting in greater FBF responses to reactive hyperemia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the present study, the degree of ERT-induced ACE inhibition was similar in NPW and HPW. Interestingly, Sumino et al 20 have recently reported that ERT increases the plasma concentration of bradykinin to a greater extent in HPW than in NPW, whereas the ERTinduced reduction in serum ACE activity was similar in NPW and HPW. We hypothesize that HPW might have higher bradykinin concentrations after ERT, resulting in greater FBF responses to reactive hyperemia.…”
Section: Discussionmentioning
confidence: 98%
“…These results are consistent with previous reports. 19,20 It is hypothesized that the long-term ERT-induced increase in PRA is due to the inhibition of ACE activity, suggesting that the production of angiotensin II is prevented, whereas PRA is increased. 21 A balance between the effects of angiotensin II and NO plays an important role in the regulation of vascular tone.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiographic left ventricular mass is greater in patients who have high nighttime ABP (33). Many studies (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) have investigated the effects of oral or transdermal HRT on BP in normotensive or hypertensive postmenopausal women. In these studies, transdermal HRT reduced 24-h ambulatory (9,15), daytime (8,10,13,14), or nighttime BP (6,7,9,10,14) without reducing office BP.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of 24-h ambulatory blood pressure monitoring (ABPM) provides more information concerning an individual's prevailing BP than conventional "office" BP measurements. In studies assessing the association between HRT and BP (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), the majority of subjects were Caucasian or African while a small number of individuals were Asian, especially Japanese. These studies have investigated the effect of HRT on BP based only on the use of office BP measurements in hypertensive or normotensive Japanese postmenopausal women (20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…10 In humans, pregnancy-related rises in oestrogen are associated with rises in ACE activity [11][12] whilst exogenous oestrogen administration to postmenopausal women (PMW) is consistently and durably associated with reduced serum ACE activity [13][14][15][16][17][18][19][20][21] with the greatest reductions amongst those with the highest initial ACE levels.…”
Section: Introductionmentioning
confidence: 99%